Exploring the Impact of Character Education and School Literacy on Students’ Learning Outcomes - Yusnita Ramanda; Rizka Harfiani; July Maini Sitepu (Ta'dib, 2025)
This study aims to analyze the influence of character education and the school literacy program on students’ Islamic Education (PAI) learning outcomes at SDN 102128 Nagaraja. Employing a quantitative ex post facto design, the research involved a saturated sample of 85 students, with data collected through validated and reliable Likert-scale questionnaires and documentation of academic scores. Data analysis included classical assumption tests and multiple linear regression using SPSS 25. The findings show that both character education and the school literacy program have a positive and significant partial effect on PAI learning outcomes, as indicated by the t-test results (t = 4.676 for character education; t = 8.268 for school literacy, both > t-table = 2.002). Simultaneously, the two variables strongly influence learning outcomes, demonstrated by an F-value of 726.549 (Sig. = 0.000), confirming the acceptance of all alternative hypotheses. The regression model (Y = 27.810 + 0.550X₁ + 0.987X₂) shows that literacy contributes the largest effect, although character education also plays an important role in shaping students’ academic performance. These results are reinforced by behavioral rubric data showing that more than 90% of students demonstrate consistent or frequent positive character traits, indicating successful internalization of character values. The study implies that strengthening literacy practices and character-building programs is essential for enhancing students’ academic achievement, particularly in religious education. It further highlights the importance of integrated school policies that combine cognitive, moral, and literacy development to support holistic learning outcomes.